Peranan Badan Perencanaan Pembangunan Daerah dalam Penyusunan Kebijaksanaan Dibidang Pembangunan di Kabupaten Tanggamus - Agus Iskandar P.P. (KEADILAN PROGRESIF, 2012)
Planning of development of area coordinated by a body namely BAPPEDA, below Regent head as regional leader holding highest chairmanship run development and governance. Problems of this research is how role of BAPPEDA in compiling wisdom planning of development in Sub-Province of Tanggamus. Approach taken is approach of empiric and normatif, using primary data and of sekunder, data analysis done with analysis qualitative. Planning of development conducted by BAPPEDA represent activity of decision making from a number of assessment choice exactly to the goal and way of which is executed utilize to reach the target of development. Role Of BAPPEDA Sub-Province of Tanggamus is to compile elementary pattern and development program, compilation of plan of APBD, research and development of town, monitoring and evaluation.